Polymer-based nuclear radiation shielding materials: state-of-the-art and emerging trends for engineering applications - Li, Xiao-Peng; Yao, Hui-Sheng; Zhao, Yue; Yuan, Bo; Zhai, Jiayu; Li, Li; Li, Heguo; Li, Xiaofeng (Frontiers in Materials, 2025)
The continuous advancement of science and technology has led to the widespread application of nuclear technology across a diverse spectrum of fields, including scientific research, industrial processes, and particularly the medical domain for diagnostics and therapeutics. This proliferation, while beneficial, necessitates stringent protective measures for personnel who may be exposed to various forms of ionizing radiation, such as X-rays, γ-rays, and neutrons. In this context, polymer-based composite materials have emerged as a pivotal class of shielding solutions. These materials are typically fabricated by incorporating functional fillers—containing elements with high atomic numbers for photon attenuation or neutron-absorbing isotopes—into a continuous polymer matrix. This design strategy synergizes the processability and lightweight nature of polymers with the superior radiation shielding efficacy of the dispersed fillers, thereby offering robust and adaptable protection for individuals in nuclear-related occupations. This paper provides a comprehensive analysis of this material system. It begins by elucidating the fundamental attenuation and shielding mechanisms that govern the interaction of radiation with matter, establishing the theoretical foundation for material design. Subsequently, the paper offers a detailed review of the development history and recent research progress in polymer-based radiation shielding, tracing its evolution from conventional lead-impregnated rubbers to modern nanocomposites. The current research status of various material types is systematically summarized, highlighting technical achievements and innovative breakthroughs, such as the use of multi-layered structures or hybrid fillers. Furthermore, the paper analyzes the critical selection criteria for polymer matrices, considering factors like radiation resistance, thermal stability, and mechanical properties. Finally, it synthesizes the key challenges that remain to be addressed in current materials and provides a forward-looking perspective on future development directions, aiming to guide subsequent research and development efforts in this critical field.